2018
DOI: 10.47354/jaes.v1i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Reading Comprehension of Descriptive Text Through Collaborative Murder

Abstract: The objectives of the research was to find out whether or not teaching of descriptive text through collaborative “MURDER” improve students’ reading comprehension at the Eighth grade students of SMP Negeri 2 Pancarijang, and to find out whether or not the students’ attitude in teaching of descriptive text through collaborative “MURDER” technique of reading comprehension at the Eighth students of SMP Negeri 2 Pancarijang. This research employed pre-experimental method that applied pre-test and post-test. The pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…As a result, the students improved in the post-test. Their findings were consistent with those of Numan (2019), Turul (2018), and Asrifan et al (2018. However, the findings contradicted those of Williams and Vaughn (2019), who reported that there was no significant difference between the means of the control and experimental groups, making research difficult.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As a result, the students improved in the post-test. Their findings were consistent with those of Numan (2019), Turul (2018), and Asrifan et al (2018. However, the findings contradicted those of Williams and Vaughn (2019), who reported that there was no significant difference between the means of the control and experimental groups, making research difficult.…”
Section: Discussionsupporting
confidence: 74%
“…Predicting: It consists of establishing adjusted and reasonable hypotheses about what will be found in the text, relying on the interpretation built on what has already been read and on the baggage of knowledge and experiences of the reader. One aspect that plays an essential role is previous knowledge and experiences, which will predict (Asrifan et al, 2018).…”
Section: Intensive Reading Strategiesmentioning
confidence: 99%
“…Reading helps gain comprehension through reading text. The importance of reading comprehension, which can assist students in finding information about the subject matter in school, general knowledge, and improve students' writing skills (Asrifan et al, 2018;Sari et al, 2020;Soto et al, 2019) explained that reading comprehension and public reading were essential skills to develop students' thinking skills and personalities in society. Moreover, the writers often found reading comprehension in English exams, school exams, and college entrance exams.…”
Section: Introductionmentioning
confidence: 99%
“…To teach reading texts, descriptive text is one of text genres is taught to the secondary school students of tenth graders. To define in short, descriptive text is a text that writes about what a person, thing, or place appearance which can also describe a situation, condition, something, and others (Asrifan, et al, 2018). Also, descriptive text is a type of text that provides information about someone or something so that readers can imagine and feel how the appearance, scenery, phenomena, and stature of a person or object in the text (Nurlaila, 2013); (Sudana, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%